Comparative study of volumetric changes and trabecular microarchitecture in human maxillary sinus bone augmentation with bioactive glass and autogenous bone graft: a prospective and randomized assessment - Pereira, R. S. [UNESP]; Menezes, J. D. [UNESP]; Bonardi, J. P. [UNESP]; Griza, G. L. [UNESP]; Okamoto, R. [UNESP]; Hochuli-Vieira, E. [UNESP] (Elsevier, 2018)
The aim of this study was to compare the volumetric changes and the new bone microarchitecture in human maxillary sinuses augmented with bioactive glass (Biogran) alone, bioactive glass combined with autogenous bone graft (1:1), or autogenous bone graft alone. Twelve maxillary sinuses were grafted with bioactive glass (group 1), nine with bioactive glass mixed with autogenous bone graft 1:1 (group 2), and 12 with autogenous bone graft (group 3). Patients underwent cone beam computed tomography 15 days after the procedure to determine the initial volume of the graft (T1) and again 6 months later (T2). Biopsies were obtained at the time of dental implant placement and were subjected to micro-computed tomography. The volumetric change was 44.2% in group 1, 37.9% in group 2, and 45.7% in group 3 (P > 0.05). The trabecular microarchitecture results showed that the materials used in groups 1 and 2 were good bone substitutes. However, the addition of 50% bioactive glass to autogenous bone graft improved the microarchitecture of the graft. Furthermore, the results for volumetric changes indicated that bioactive glass, its association with autogenous bone graft in a 1:1 ratio, and autogenous bone graft alone have similar resorption.
Keywords: bioactive glass; bioactive glass added to autogenous bone graft; bone graft resorption; maxillary sinus augmentation; trabecular bone microarchitecture